Observe, Dismember, Overcome: "Resident Evil 4" (2005; 2023) and "Dead Space" (2008; 2023) as Video Game Extensions of the Body Horror Subgenre - Baran, Paweł (Zagadnienia Rodzajów Literackich, 2025)
Body horror, which is very often defined as a cinematic subgenre (Cherry 2009, Weismann 2021), utilizes themes of mutation, infection etc. to play on resentment towards human form. Emerging prominently in the 1970s and 1980s and shaped by new filmmaking technologies and sociopolitical upheavals, body horror became synonymous with cinema. Cronenberg and Carpenter took part in conquering, in a way, the subgenre through iconic films like The Fly (1986) and The Thing (1982). While some look for the roots of body horror in earlier literary traditions (Reyes 2024), its characteristics solidified in the cinema of late 20th century. Surfacing of body horror in other media, however, opens possibilities of analysing the subgenre beyond film, e.g., in video games. The aim of this paper is to demonstrate how Resident Evil 4 (Capcom 2004; 2023) and Dead Space (Visceral 2008; Motive Studio 2023) extend body horror through game mechanics. The notion of “extended body genre” (Perron 2009), is based on the unity of perception and performance between the player and the character. Survival horror video games utilize interactivity and player agency to extend the experience. Through a grisly sounding „peeling system” (Motive Studio 2023), or combat mechanics, both analysed games emphasise and extend the body horror. What is notable is the fact that both these games force the players to enact the violence and mutilation on the diegetic world. The classic status quo on acting on the audience is accompanied by the new tendency to let it partake in the maiming. Both of the analysed titles also contain gameplay incentives to observe mutations and alike in full effect. Like the characters of the famous body horror films, players in Dead Space and Resident Evil 4, have to analyse the extent of mutation in their foes and come up with tactics to fight off the monstrosities.